Improving the efficiency of a Cu2ZnSn(S, Se)4 solar cell using a non-toxic simultaneous selenization/sulfurization process. (1st March 2018) - Wang, Li-Ching; Lin, Yi-Cheng; Hsu, Hung-Ru
Abstract: This paper proposes a simple non-toxic simultaneous selenization/sulfurization process to improve cell efficiency in Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells with the aim of modulating the S/(S+Se) ratio. Experiment results show that the S content in the thin film increases with the S/(S+Se) ratio, and the S content on the surface is higher than inside the device when S/(S+Se) ratio ≧ 0.55. Higher S content on the surface results in a V-shaped energy gap profile. The simultaneous selenization/sulfurization process was shown to inhibit the formation of an excessively thick interfacial MoSe2 /Mo(S, Se)x layer, while enhancing the uniformity of Cu, Zn and Sn distribution in the absorber layer. The Zn/Sn ratio of the CZTSSe absorber layer was shown to decrease with an increase in the S/(S+Se) ratio, thereby increasing the likelihood that secondary phases of SnSe2, CuSn(S, Se), ZnS, SnS and Cu2 SnS3 will form in the absorber layer. Conductive atomic force microscopy (C-AFM) results revealed that secondary phases of SnSe2 and Cu2 Sn(S, Se)3 on the surface of the film increased the number of leakage current pathways along the grains of secondary phases. The proposed simultaneous selenization/sulfurization method increases device efficiency from 5.2% (conventional non-toxic selenization) to 6.3% when S/(S+Se) = 0.55. Graphical abstract: